Getting to the heart of the matter: an ethnography of emotions and emotion regulation in cardiac rehabilitation. Issue 3 (27th May 2019) - Meredith, Samantha J.; Wagstaff, Christopher R. D.; Dicks, Matt
ABSTRACT: Considering the detrimental impact of emotional suffering on patient recovery (e.g. increased mortality rates), a key component in rehabilitation settings should be the promotion of psychosocial health. Research has shown cardiac rehabilitation (CR) to decrease anxiety and depression, enhance emotional well-being and reduce the deleterious effects of negative emotions on prognosis. Nevertheless, limited attention has been given to heart disease as a lived experience and the presence of the patient's voice in CR is negligible. Using an ethnographic approach, the aim of the current research was to provide a penetrative insight into the social and psychological environment of a CR setting in the United Kingdom. Three main methods were used to collect data over a 12-month period, including participant observation (225 h), informal and formal interviews, and a reflexive diary. Thematic analysis was used to generate patterns (themes) in the data. Following thematic development, ethnographic creative non-fiction was adopted to fashion non-fictional stories grounded in real events and patients' lived experiences. Three composite narratives illustrated the emotional intensity of recovering from a cardiac event and highlighted the value of CR to aid patients with reskilling and emotional support. In discussing our data, we emphasise the potential value of emotional intelligent care provision, and the creation of an environment that encourages emotional disclosure. We conclude with a discussion of the value of narrative medicine as a pedagogical tool for CR staff and patients.